Influence of stripe rust infection on the photosynthetic characteristics and antioxidant system of susceptible and resistant wheat cultivars at the adult plant stage - Chen, Yang-Er; Cui, Jun-Mei; Su, Yan-Qiu; Yuan, Shu; Yuan, Ming; Zhang, Huai-Yu (Frontiers in Plant Science, 2015)
Wheat stripe rust (Puccinia striiformis f. sp. tritici) is one of the most serious diseases of wheat (Triticum aestivum L.) worldwide. To gain a better understanding of the protective mechanism against stripe rust at the adult plant stage, this study investigated the differences in photosystem II (PSII) and antioxidant enzymatic systems between susceptible and resistant wheat in response to stripe rust disease caused by Puccinia striiformis. We found that chlorophyll fluorescence and the activities of the antioxidant enzymes were higher in resistant wheat than in susceptible wheat after stripe rust infection. Compared with the susceptible wheat, the resistant wheat accumulated a higher content of D1 protein and a lower level of reactive oxygen species (ROS) after infection. Further, this is the first study to demonstrate that D1 and LHCII phosphorylation are involved in the resistance to stripe rust in wheat. In addition, we found that CP29 was phosphorylated under stripe rust infection; CP29 is also phosphorylated in monocots under other environmental stresses. Furthermore, the thylakoid structure showed more extensive damage in the susceptible wheat compared with that observed in the resistant wheat. Therefore, these findings provide evidence that thylakoid protein phosphorylation and antioxidant enzyme systems play an important role in plant responses and defense mechanisms in wheat cultivars subject to this type of biotic stress.